Zambia : The Enterprise Development Project - Mohan, P.C. (World Bank, Washington, DC, 2012)
The Enterprise Development Project (EDP) - 1998-2003 - was designed to support, with a credit of US$ 45 million, Zambia's Economic Reform Program that began in 1991. One of the key aspects of this reform program was to dismantle traditional state-supported enterprise development mechanisms and replace these with market-determined enterprise development structures. Three specific objectives were identified : (i) enhancing Zambian firms' technical know-how by providing demand-driven assistance to Zambian firms in the form of matching grants; (ii) enhancing Zambian firms' access to finance by providing a long-term credit facility for investments and a short-term credit line for exporters; and (iii) strengthening the financial system and availability of information resources in Zambia by providing technical assistance to help strengthen the institutional underpinnings of the financial system at the wholesale, retail and regulatory levels.